Common European harmful algal blooms affect the viability and innate immune responses of Mytilus edulis larvae. Issue 1 (November 2015) - De Rijcke, M.; Vandegehuchte, M.B.; Vanden Bussche, J.; Nevejan, N.; Vanhaecke, L.; De Schamphelaere, K.A.C.; Janssen, C.R.
Abstract: Like marine diseases, harmful algal blooms (HABs) are globally increasing in frequency, severity and geographical scale. As a result, bivalves will have to face the combined threat of toxic algae and marine pathogens more frequently in the (near) future. These stressors combined may further affect the recruitment of ecologically and economically important bivalve species as HABs can affect the growth, viability and development of their larvae. To date, little is known on the specific effects of HABs on the innate immune system of bivalve larvae. This study therefore investigates whether two common harmful algae can influence the larval viability, development and immunological resilience of the blue mussel Mytilus edulis . Embryos of this model organism were exposed (48 h) to five densities of Pseudo-nitzschia multiseries or Prorocentrum lima cells. In addition, the effect of six concentrations of their respective toxins: domoic acid (DA) and okadaic acid (OA) were assessed. OA was found to significantly reduce larval protein phosphatase activity (p < 0.001) and larval viability (p < 0.01) at concentrations as low as 37.8 μg l −1 . P. multiseries (1400 cells ml −1 ), P . lima (150 cells ml −1 ) and DA (dosed five times higher than typical environmental conditions i.e. 623.2 μg l −1 ) increased the phenoloxidase (PO) innate immune activity of the mussel larvae. These results suggest that the innate immune response of even the earliest life stages of bivalves is susceptible to the presence of HABs. Highlights: Larvae of Mytilus edulis were exposed to two common harmful algae and their toxins. 48 h exposure to environmentally relevant concentrations affects bivalve larvae. Okadaic acid inhibits protein phosphatase activity and reduces the larval viability. Harmful algal blooms trigger phenoloxidase innate immune responses of bivalve larvae.